Anxiety Level of Ovarian Cancer Patients After Being Given SEFT (Spiritual Emotional Freedom Technique) - Anik Latifah; Elok Yunita Sari (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2024)
Ovarian cancer is the case with cancer most common cancer in the world, with 240,000 new cases every year. There are three ways to respond emotionally to cancer patients that are rejection, anxiety, stress, and even depression. As many as 28.8 percent of cancer patients experience anxiety. When anxiety is not handled, it can even cause stress and depression that influence the expectations and quality of life of patients. Spiritual Emotional Freedom Technique (SEFT) is therapy That uses spiritual elements to reduce psychological and physical problems caused by emotional or psychosomatic causes. Research purposes: This is to analyze the worried patient's ovarian cancer level after SEFT. Type research used in research​ This is a quantitative study with the method pre-experimental approach One Group Pretest- Posttest Where the population in this study is patients with ovarian cancer at the Indonesian Cancer Foundation, East Java Coordinating Branch—taking sample done with technique Purposive sampling according to the inclusion criteria with a total of 26 patients. Intervention therapy SEFT is done 4-5x times each Sunday for two weeks. The instruments used were the HARS questionnaire sheet, observation sheet, and SOP for implementing SEFT. The data analysis used is the parametric Paired T-test. The result obtained is P -value equal 0.000 less than (alpha equal 0.05), which means that H0 is rejected and H1 is accepted. Where the conclusion is that the Spiritual Emotional Freedom Technique (SEFT) affects reducing anxiety if done regularly and continuously. The intervention focuses on reducing problem psychological Problems caused by emotional or psychosomatics. So, the body will experience relaxation, and the patient will become calm.